High-throughput miRNA sequencing of the human placenta: expression throughout gestation - Gonzalez, Tania L (Epigenomics, 2021)
AIM: To understand miRNA changes across gestation in healthy human placentae. This is essential before miRNAs can be used as biomarkers or prognostic indicators during pregnancy. MATERIALS & METHODS: Using next-generation sequencing, we characterize the normative human placenta miRNome in first (n = 113) and third trimester (n = 47). RESULTS & CONCLUSION: There are 801 miRNAs expressed in both first and third trimester, including 182 with similar expression across gestation (p ≥ 0.05, fold change ≤2) and 180 significantly different (false discovery rate <0.05, fold change >2). Of placenta-specific miRNA clusters, chromosome 14 miRNA cluster decreases across gestation and chromosome 19 miRNA cluster is overall highly expressed. Chromosome 13 clusters are upregulated in first trimester. This work provides a rich atlas of healthy pregnancies to direct functional studies investigating the epigenetic differences in first and third trimester placentae.